Fatores responsáveis pela alta rotatividade na Secretaria de Obras da Prefeitura de Pinhais - Souza, Grasiele de (2012)
The organizations depend more and more of the people that in him work for guarantee his productivity and profit value and that become possible with the permanence of them in the organization. In that sense is important the constant monitoring of the human resources for control of the turnaround in the environment of work, aiming at always the quality of life of those collaborators. This study aims to compare the indices of turnaround between the market of the civil construction and the Sector of Works of the city Hall of Pinhais PR, identifying which are the main factors of this phenomenon, using a documentary research through exit interviews and research of organizational climate and bibliographical references for propose an assembly of suggestions for the main responsible factors by the high work hand turnaround in the sector of works of the city Hall of Pinhais, adapted The reality of this town. The results showed that, of a general form, the collaborators perceive the organizational climate of the Sector of Works of the city Hall of Pinhais of positive form in some aspects. On the other hand, detaches-itself a high turnaround by dissatisfaction of the collaborators regarding the absence of social benefits and incentive to the professional growth of that functional chart.